PERILAKU IBU RUMAH TANGGA PENGGUNA KREDIT BARANG MINDRING DI JORONG LUBUAK MUARO NAGARI SUNGAI ABU - Nofika, Elfi; Rahmadani, Sri; Yatim, Yenita (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Household life cannot be separated from economic activities, one of which is in conducting transactions. Transactions that are often carried out by housewives are goods credit transactions. This is done because with credit, housewives can get goods without having to have enough money first. So that the desire to meet the needs can be achieved in a short time. The purpose of this study is to analyze the behavior of housewives who use mindring credit in Jorong Lubuak Muaro, Nagari Sungai Abu. The theory used in this study is the theory of social action proposed by Max Weber. The research was conducted in Joronng Lubuak Muaro, Nagari Sungai Abu, Hiliran Gumanti District, Solok Regency. This research used qualitative research methods with descriptive research type. Withdrawal of informants was carried out by purposive sampling technique, with the informants being housewives who made mandring goods loans. The data collection method in this study begins with observation, interviews, and document studies. Data analysis was carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that there were several behaviors of housewives in using credit items including, 1) buying goods because they were needed, 2) buying goods because of consumptiveness, 3) ease of obtaining goods, and 4) buying goods because of the influence of the social environment, as well as their behavior. Housewife When Paying Credit Bills.